Define Electronic Enterprise Financial Management Information Decision-Making Process Based on IoT and the ERP Model. (19th September 2022) - Su, Huiling
Abstract : In order to realize the financial quality management of listed energy companies and realize the economical development of enterprises, the author proposes a refined evaluation method for the financial management quality of listed energy companies based on the Internet of Things and the ERP model. By introducing the concept of IoT, ERP and the financial characteristics of listed energy companies select an energy power supply enterprise as a pilot unit, combine the development strategy and the current challenges, and conducting a comprehensive analysis of the process and effect of its implementation of the financial management system, this reflects the superiority of the refined evaluation method of financial management quality of listed energy companies based on the Internet of Things and the ERP model. Pilot experiments show that, comparing before the pilot program, the financial operation status of listed companies has increased by 13.59% in total assets, positive growth achieved. The refined evaluation method of the financial management quality of listed energy companies based on the Internet of Things and the ERP model can realize the economic development of enterprises.